Perencanaan Sistem Distribusi Air Bersih Berbasis Risiko di Kawasan Geopark Ciletuh - Ihsan Maulandi; Asep Supriatna (Institut Nalanda, 2026)
Clean water is a fundamental human need that supports public health, social activities, and sustainable economic development. Desa Girimukti, located in the UNESCO Global Geopark Ciletuh–Palabuhanratu area, faces increasing clean water demand due to population growth and tourism development, while also being exposed to environmental and operational risks such as landslides, floods, and source reliability issues. This study aims to plan a risk-based clean water distribution system capable of ensuring service reliability and sustainability. The research applied a quantitative–descriptive approach, including population projection, water demand analysis, risk identification, and hydraulic analysis using the Hazen–Williams equation. The results indicate that the projected water demand at the end of the planning period is approximately 9 L/s, while the available water sources from groundwater wells and surface water provide sufficient capacity. Risk analysis shows that surface water pollution represents the highest risk, requiring appropriate treatment and mitigation measures. The designed centralized distribution system with a main reservoir meets technical criteria for velocity, headloss, and residual pressure. Overall, the proposed system is technically feasible and capable of mitigating key risks in the study areaThe abstract briefly contains a description of the problem and research objectives, methods used, and research results.